Carrier Lifetimes and Influence of In-Grown Defects in N-B Co-Doped 6H-SiC - Grivickas, Vytautas; Gulbinas, Karolis; Jokubavicius, Valdas; Sun, Jianwu; Karaliūnas, Mindaugas; Kamiyama, Satoshi; Linnarsson, Margareta K.; Kaiser, Michl; Wellmann, Peter; Syväjärvi, Mikael (IOP Conference Series: Materials Science and Engineering, 2014)
The thick N-B co-doped epilayers were grown by the fast sublimation growth method and the depth-resolved carrier lifetimes have been investigated by means of the free-carrier absorption (FCA) decay under perpendicular probe-pump measurement geometry. In some samples, we optically reveal in-grown carbon inclusions and polycrystalline defects of substantial concentration and show that these defects slow down excess carrier lifetime and prevent donor-acceptor pair photoluminescence (DAP PL). A pronounced electron lifetime reduction when injection level approaches the doping level was observed. It is caused by diffusion driven non-radiative recombination. However, the influence of surface recombination is small and insignificant at 300
Keywords: SiC; sublimation growth; carrier lifetime; co-doped epilayers